A comparison between occlusive and exposure dressing in the management of burn wound. Issue 3 (May 2016) - Soltan Dallal, M.M.; Safdari, R.; Emadi Koochak, H.; Sharifi-Yazdi, S.; Akhoondinasab, M.R.; Pourmand, M.R.; Hadayatpour, A.; Sharifi-Yazdi, M.K.
Highlights: Exposure dressing of burn wounds was more susceptible to contamination than occlusive dressing. The mean duration of treatment based on epithelialization and healing in occlusive dressing was longer than that for exposure dressing. The incidence of burns due to hot liquid was higher than burns of other etiologies. Pseudomonas aeruginosa was the most common organism encountered in burn infection. Abstract: Background and aim: Two types of dressing, occlusive and exposure dressing, are commonly used in burn units. A dressing is said to be occlusive if a moist wound surface is maintained when the dressing is in place. This study was designed to compare the effectiveness of occlusive and exposure dressing in controlling burn infections. Patients and methods: Two hundred patients with second-degree burns admitted to Mottahari Hospital, Tehran, Iran, over a period of 12 months from May 2012 to May 2013 were studied. They were divided into two groups of 100 each, to receive either occlusive or exposure dressing. During the first week of treatment, wound specimens were obtained by sterile swab and cultured in selective media. Demographics (age and gender), burn areas, cause of burn, length of hospital stay (LOS), type of infections and time to total healing were compared between the two groups. Results: Occlusive dressing was more susceptible to microbial contamination and infections than exposure dressing. The mean duration of treatment based on epithelialization and healing in occlusive dressing was longer than for exposure dressing. The most common isolate was Pseudomonas spp., followed by Enterobacter, Escherichia coli, Staphylococcus aureus, Acinetobacter, and Klebsiella spp. Conclusions: Exposure dressing was more suitable than occlusive dressing for treating partial-thickness at our center. Pseudomonas aeruginosa was the most common organism encountered in burn infection.